Pengaruh Aksesibilitas dan Sales Promotion Terhadap Kunjungan Wisata Olahraga JSC Bowling Center - Marchelino, Wendy; Widagdo, Herry (MDP Student Conference, 2024)
The aim of this research is to evaluate the impact of Accessibility and Sales Promotion on the Decision to Visit the JSC Bowling Center Sports Tourism, both partially and simultaneously. The data collection method applied involved distributing questionnaires to 392 respondents. This research uses descriptive research, with a non-probability sampling technique using the purposive sampling method and supported by the SPSS 25 application. The results of the research show that the partial test (t-test) shows a positive and significant impact of the Accessibility and Sales Promotion variables on the decision to visit. Meanwhile, the simultaneous test (F-test) proves that the independent variables, namely Accessibility and Sales Promotion, positively and significantly influence the dependent variable, namely the decision to visit.